Recent Advances in Biological Active Sulfonamide based Hybrid Compounds Part C: Multicomponent Sulfonamide Hybrids - Ghomashi, Reihane; Ghomashi, Shakila; Aghaei, Hamidreza; Massah, Samineh; Massah, Ahmad R. (Current Medicinal Chemistry, 2023)
Sulfonamides, with the general formula R-SO2NR1R2, have attracted great attention since the early discovery of sulfonamide-containing antibacterial drugs. The combinations of certain sulfonamides and other drug molecules to form sulfonamide hybrids are being used to develop novel formulations with greater effectiveness and in a huge range of therapeutic applications such as antimicrobial, antifungal, anti-inflammatory, antitubercular, antiviral, antidiabetic, antiproliferative, carbonic anhydrase inhibitor, antimalarial, anticancer and other medicinal agents. Part C of this review presents recent advances in designing and developing multicomponent sulfonamide hybrids containing more than one biologically active heterocycle, such as coumarin, indole, pyridine, pyrimidine, pyrazole, triazole, oxazole, oxadiazole, triazine, quinazoline, and thiadiazol. This review aims to highlight the status of the hybridization technique in synthesizing biological and computational studies of novel sulfonamide hybrids that were designed and presented between 2016 and 2020.
Keywords: multicomponent